Investigating the long-term impact of a programme of mindfulness combined with exercise delivered online (MOVE) on individuals living with chronic pain-an exploratory one-year follow-up of a feasibility randomised control trial - Orla Deegan; Mai Yoshitani; Brona Fullen; Maria Gordon; Orla McDonagh; Orlaith Sheerin; Jane Murphy; Oreluwa Oyebode; Ricardo Segurado; Conor Hearty; Maire Brid Casey; Catherine Doody (PLoS ONE, 2025)
Background Online pain management programmes have evidence as effective interventions for individuals with chronic pain. This study was a one-year exploratory follow-up of a parallel group feasibility randomised controlled trial (RCT) investigating the effectiveness of participating in an online pain management programme that combined Mindfulness-Based Stress Reduction (MBSR) and exercise delivered online for individuals living with chronic pain (MOVE). Methods Ninety-six individuals with chronic pain participated in an eight-week feasibility RCT comparing MBSR and exercise to an online self-management guide. Fourteen patient reported outcome measures (PROMS) were collected at baseline, post-intervention, three months post-intervention and at a one-year follow-up. Analysis of changes in PROMs between baseline and one-year follow-up in the current study were analysed using Student’s t-tests, and in addition, data were analysed using linear mixed models, examining effect sizes. Results Forty-eight participants completed PROMs at a one-year follow-up. Small between group differences were observed in depression and the mental health component of the health-related quality of life score, in favour of the combined MBSR and exercise group. A further nine PROMS showed improvements in favour of the self-management group (SM). In the MOVE group, one-year follow-up scores demonstrated trends towards improvement compared to baseline scores for 10/14 PROMs. In the SM group positive changes were found in 13/14 PROMs. At one-year follow-up, results from the Patients Global Impression of Change Scale, demonstrated that 63.3% of participants in the combined mindfulness and exercise group, and 44.4% of participants in the self-management group reported improvement with a noticeable change. Conclusions The results of this long-term exploratory study suggest no significant difference between groups for the investigated PROMs at one-year follow-up. A fully powered RCT examining the effectiveness of MBSR combined with exercise delivered in a live synchronous online format is warranted, to explore the factors to optimise long-term outcomes for people living with chronic pain.